Utilization of Microfluidic Device for Determination of Nitrite and Nitrate in Water and Soil Samples - Laitip, N.; Chomnawang, N.; Youngvises, N.; Threeprom, W. (Asian Journal of Chemistry, 2013)
A miniaturized system for determination of nitrite and nitrate by microfluidic device with chemiluminescence detection has been described. This method is based on chemiluminescence reaction produced by oxidation of nitrite with hydrogen peroxide in acid medium in the presence of alkaline luminol. The sequential determination of nitrite and nitrate utilized an off-line photolytic reduction of nitrate to nitrite was applied incorporating with EDTA as an activator. Efficiency of the photo-conversion was satisfactory good with 47-52 % of conversion. The optimized condition provided a linearity range between 0.5-100 μM for nitrite and 1.0-100 μM for nitrate. The detection limit for nitrite and nitrate were 2.1 × 10-2 μM and 9.3 × 10-2 μM, respectively. The precision of the method was satisfactory good with % RSD of 5 μM of nitrite and 10 μM of nitrate were less than 3.3 and 3.6 %, respectively (n = 10). The potential ion interferences namely Fe2+, Fe3+, Cu2+ and Mn2+ were completely eliminated by on-line passing through the samples on cation exchange column. This proposed method was successfully applied for quantitative analysis of nitrite and nitrate in environmental water samples and agricultural soil samples with desirable recovery ranging from 85 to 110 %.